The best ball - Homberg, Ruth; Disney Enterprises (1996-); Disney Storybook Artists (New York Random House, 2017)
Pumpkin the puppy, Sultan the tiger, Petite the pony, and the rest of the Disney Palace Pets come together to throw a ball. Will they be ready in time?
"Based on the animated short written by Shea Fontana."
At head of title: Disney
English Stories
Preschool-Kindergarten
Keywords: Balls (Parties) -- Juvenile fiction; Pets -- Juvenile fiction; Picture books for children; Animals -- Fiction; Balls (Parties) -- Fiction; Friendship -- Fiction; Balls (Parties) -- Juvenile fiction; Balls (Sporting goods) -- Juvenile fiction; Balls (Parties); Pets; Picture books for children; Readers (Primary); Early Reader; Fiction; Juvenile works; Readers (Elementary); Readers (Elementary)